Tissue Insulin Sensitivity in Aging: A Large-Scale PET Study of Skeletal Muscle, Adipose Tissue, Myocardium and Liver - Leppähaara, Wilhelmina (My University, 2026)
Context Aging and insulin resistance are both characterized by unfavorable changes in body composition, insulin receptor expression and activity and metabolic flexibility. However, it remains unclear how aging independently affects tissue-specific insulin sensitivity in humans. Methods We examined the association between age and insulin-stimulated glucose uptake, measured with [18F]fluorodeoxyglucose ([18F]FDG) positron emission tomography (PET) during hyperinsulinemic, euglycemic clamp in a cross-sectional cohort of 503 individuals who participated in clinical research studies in Turku PET Centre (Turku, Finland) between 1997 and 2023. Results Aging was associated with reduced whole-body insulin sensitivity (M value, β = -0.177, P < .0001). This was primarily driven by impaired insulin-mediated suppression of endogenous glucose production (β = 0.094, P = .001), and decreased glucose uptake in subcutaneous adipose tissue (β = -0.104, P < .0001), but not in skeletal muscle (P = .31). In the liver and myocardium, higher age associated with increased glucose uptake (β = 0.116, P = .0002 and β = 1.159, P = .041, respectively). Aging had a more significant association with whole-body and visceral adipose tissue glucose uptake in men, while no sex-specific differences were observed in other tissues. Conclusions Aging affects glucose metabolism primarily in adipose tissue and the liver, while skeletal muscle glucose uptake appears to be more dependent on other contributors to insulin resistance, such as the co-existence of type 2 diabetes.
Keywords: insulin resistance; glucose metabolism; positron emission tomography